Acetylation-induced proteasomal degradation of the activated glucocorticoid receptor limits hormonal signaling - Aishwarya Iyer-Bierhoff; Martin Wieczorek; Sina Marielle Peter; Dima Ward; Martin Bens; Sabine Vettorazzi; Karl-Heinz Guehrs; Jan P. Tuckermann; Thorsten Heinzel (iScience, 2024)
Summary: Glucocorticoid (GC) signaling is essential for mounting a stress response, however, chronic stress or prolonged GC therapy downregulates the GC receptor (GR), leading to GC resistance. Regulatory mechanisms that refine this equilibrium are not well understood. Here, we identify seven lysine acetylation sites in the amino terminal domain of GR, with lysine 154 (Lys154) in the AF-1 region being the dominant acetyl-acceptor. GR-Lys154 acetylation is mediated by p300/CBP in the nucleus in an agonist-dependent manner and correlates with transcriptional activity. Deacetylation by NAD+-dependent SIRT1 facilitates dynamic regulation of this mark. Notably, agonist-binding to both wild-type GR and an acetylation-deficient mutant elicits similar short-term target gene expression. In contrast, upon extended treatment, the polyubiquitination of the acetylation-deficient GR mutant is impaired resulting in higher protein stability, increased chromatin association and prolonged transactivation. Taken together, reversible acetylation fine-tunes duration of the GC response by regulating proteasomal degradation of activated GR.